Texas blue - Thomas, Jodi (New York : Berkley Books, 2011)
Determined to marry into a respectable family, gambler Lewton Paterson, sets his sights on Emily McMurray, one of the McMurray sisters. Unfortunately, Emily has no intention of ever getting married, especially to a man like Lewt.
Keywords: Gamblers; Man-woman relationships; Gambling; Ranch life -- Texas; Texas; Love stories; Historical fiction; Large type books